2007
DOI: 10.1016/j.pain.2006.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamus and amygdala response to acupuncture stimuli in carpal tunnel syndrome

Abstract: Brain processing of acupuncture stimuli in chronic neuropathic pain patients may underlie its beneficial effects. We used fMRI to evaluate verum and sham acupuncture stimulation at acupoint LI-4 in Carpal Tunnel Syndrome (CTS) patients and healthy controls (HC). CTS patients were retested after 5 weeks of acupuncture therapy. Thus, we investigated both the short-term brain response to acupuncture stimulation, as well as the influence of longer-term acupuncture therapy effects on this short-term response. CTS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
153
1
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(169 citation statements)
references
References 52 publications
(56 reference statements)
7
153
1
8
Order By: Relevance
“…25 It has been reported that SI processing is performed with input provided by mechanoreceptors, 26 but the activation of much of the SI has not been conˆrmed by acupuncture stimulation. 1,2,[4][5][6][7][8][10][11][12][13][14] The peripheral receptors involved in acupuncture stimulation have been suggested to be the polymodal receptors that are nociceptive receptors of the C-ˆbers. 27 It is also thought that the input is the transmission through C-ˆber in response to production of a chemical substance following deep tissue injury by manual acupuncture stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 It has been reported that SI processing is performed with input provided by mechanoreceptors, 26 but the activation of much of the SI has not been conˆrmed by acupuncture stimulation. 1,2,[4][5][6][7][8][10][11][12][13][14] The peripheral receptors involved in acupuncture stimulation have been suggested to be the polymodal receptors that are nociceptive receptors of the C-ˆbers. 27 It is also thought that the input is the transmission through C-ˆber in response to production of a chemical substance following deep tissue injury by manual acupuncture stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 20 years, the development of imaging techniques, such as functional magnetic resonance imaging (fMRI), has opened the door for the study of brain activity in response to acupuncture stimulation. Numerous studies have been performed with fMRI and a variety of acupuncturerelated stimulations, such as electroacupuncture, 1,2 manual acupuncture, [1][2][3][4][5][6][7][8][9][10][11][12][13] sham acupuncture of the skin some distance from a known acupoint [4][5][6] or by noninsertive acupuncture and poking of the skin over an acupuncture point, [7][8][9][10][11] pressure to the acupoint, 12 laser acupuncture, 13 and electrical acupoint stimulation. 14 fMRI studies of acupuncture have typically utilized a block design that is used as a general linear model regressor in the analysis of fMRI data based on the assumption that mechanoreceptors and nociceptor-associated aŠerence work coincidentally with acupuncture stimulation, which is the conscious perception and evaluation of this aŠerence.…”
Section: Introductionmentioning
confidence: 99%
“…During this resting state, recall, thoughts about the future, and thoughts about alternatives to current situations may occur. 27,55 Acupuncture has been recognized as being modulatory of the DMN. 17,29,30,[55][56][57] In this study, we have evidence of DMN modulation by low-intensity laser acupuncture, and there is emerging evidence regarding the role of the DMN in depression.…”
Section: Modulation Of the Default Mode Networkmentioning
confidence: 99%
“…27,55 Acupuncture has been recognized as being modulatory of the DMN. 17,29,30,[55][56][57] In this study, we have evidence of DMN modulation by low-intensity laser acupuncture, and there is emerging evidence regarding the role of the DMN in depression. 30,55 It is possible that modulation of the DMN may be one mechanism by which acupuncture produces its antidepressant effect.…”
Section: Modulation Of the Default Mode Networkmentioning
confidence: 99%
“…There have been many studies [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] some of which have involved functional magnetic resonance imaging (fMRI) and positron emission tomography (PET) of the brain effects of needle acupuncture. Some neuroimaging and neuroendocrine studies have suggested that needle acupuncture affects hypothalamic as well as extrahypothalamic functions and modulates mood [3,[5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%